Pengaruh Model Mind Mapping terhadap Kemampuan Membaca Pemahaman - Heru, Agus (Lentera: Jurnal Ilmiah Kependidikan, 2017)
The aim of this study is to determine whereas mind mapping influence students reading comprehension grade VII at SMP Negeri 1 Mesuji Makmur. This study uses an experimental method. Data collection techniques is used in this study are engineering test and documentation, while the data analysis technique used is the t-test calculation. Based on the research that has been conducted using mind mapping models, the value of the average grade of 79.1 experimental class is greater than the average value of the control class is 67, 15. Hypothesis test obtain that t = 5.66, where t is higher than table = 1.99 so it can be concluded that there is an effect of Mind Mapping against Reading Comprehension ability Seventh Grade Students of SMP Negeri 1 Mesuji Makmur.